One-volt-driven superfast polymer actuators based on single-ion conductors - Onnuri Kim; Hoon Kim; U. Hyeok Choi; Moon Jeong Park (Nature Communications, 2016)
Achieving a balance of desirable mechanical properties with low power consumption is important for developing soft actuator technologies. Here, the authors report single-ion-conducting polymers that function as fast, durable actuators at low voltages.